Does the hearing sensitivity in thorny catfishes depend on swim bladder morphology? - Angelika Zebedin (Public Library of Science (PLoS), 2013)
Background Thorny catfishes exhibit large variations in swim bladder morphology. These organs are of different sizes, forms and may have simple or branched diverticula. The swim bladder plays an important role in otophysans because it enhances their hearing sensitivity by transmitting sound pressure fluctuations via ossicles to the inner ear. Methodology/principal findings To investigate if a form-function relationship exists, the swim bladder morphology and hearing ability were analyzed in six species. The morphology was quantified by measuring the length, width and height and calculating a standardized swim bladder length (sSBL), which was then used to calculate the relative swim bladder length (rSBL). Hearing was measured using the auditory evoked potential (AEP) recording technique. Two species had simple apple-shaped and four species heart-shaped (cordiform) bladders. One of the latter species had short unbranched diverticula on the terminal margin, two had a secondary bladder and two had many long, branched diverticula. The rSBL differed significantly between most of the species. All species were able to detect frequencies between 70 Hz and 6 kHz, with lowest thresholds found between 0.5 and 1 kHz (60 dB re 1 µPa). Hearing curves were U-shaped except in Hemidoras morrisi in which it was ramp-like. Mean hearing thresholds of species possessing smaller rSBLs were slightly lower (maximum 8.5 dB) than those of species having larger rSBLs. Conclusions/significance The current findings reveal a relationship between swim bladder form and its function among thorny catfishes. Relatively smaller swim bladders resulted in relatively better hearing. This is in contrast to a prior inter-familial study on catfishes in which species with large unpaired bladders possessed higher sensitivity at higher frequencies than species having tiny paired and encapsulated bladders.